2020
DOI: 10.1111/jfs.12788
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ultraviolet light‐C and clove essential oil to inactivate SalmonellaTyphimurium biofilms on stainless steel

Abstract: Salmonella typhimurium is able to form biofilms as a resistance mechanism against antimicrobials; therefore, it represents a problem for assuring food safety and highlights the importance of research on anti‐biofilm technologies. In this study, S. typhimurium biofilms were inactivated with the combination of clove essential oil (CEO) and ultraviolet light (UV‐C). The volatile composition of the CEO determined by gas chromatography showed eugenol as the major constituent (82%). A combination of CEO with UV‐C ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…For example, citrus lemon (CLEO) and C. reticulata oils (CREO) combined with heat treatment affected almost the entire cell population (up to 99%) of Levilactobacillus brevis and Leuconostoc mesenteroides , while with exposure to CLEO and CREO alone, the cell populations with physiological damage were in a range of 19.6–66.8% and 23.8–75.9%, respectively [ 54 ]. Synergistic antimicrobial effects generated by UV light and EOs were also reported, and it has been demonstrated that UV-C light enhanced the antibacterial activity of clove oil against S. Typhimurium by inactivating the biofilms on stainless steel [ 55 ]. High hydrostatic processing (HPP) is one of the extensively explored nonthermal food processing technologies, which has great potential to preserve the freshness of food without affecting the food quality characteristics, such as the color, natural flavor, and nutrients, in addition to directly killing fish-spoiling bacteria, such as L. monocytogenes , E. coli , and V. parahaemolyticus .…”
Section: Synergistic Effect Of Essential Oils With Physical Methodmentioning
confidence: 99%
“…For example, citrus lemon (CLEO) and C. reticulata oils (CREO) combined with heat treatment affected almost the entire cell population (up to 99%) of Levilactobacillus brevis and Leuconostoc mesenteroides , while with exposure to CLEO and CREO alone, the cell populations with physiological damage were in a range of 19.6–66.8% and 23.8–75.9%, respectively [ 54 ]. Synergistic antimicrobial effects generated by UV light and EOs were also reported, and it has been demonstrated that UV-C light enhanced the antibacterial activity of clove oil against S. Typhimurium by inactivating the biofilms on stainless steel [ 55 ]. High hydrostatic processing (HPP) is one of the extensively explored nonthermal food processing technologies, which has great potential to preserve the freshness of food without affecting the food quality characteristics, such as the color, natural flavor, and nutrients, in addition to directly killing fish-spoiling bacteria, such as L. monocytogenes , E. coli , and V. parahaemolyticus .…”
Section: Synergistic Effect Of Essential Oils With Physical Methodmentioning
confidence: 99%
“…Moreover, S. Typhimurium biofilms were eliminated (6.8 logs CFU/cm 2 ) through the combination of clove EO (1.2 mg/mL) and UV-C (76.41 mJ/cm 2 ) on stainless steel, demonstrating a synergistic effect. EO reduced only 1.8 log CFU/cm 2 when used individually, while UV-C reduced 2.9 log CFU/cm 2 (Silva- Espinoza et al, 2020).…”
Section: Essential Oils and Ultraviolet Lightmentioning
confidence: 99%
“…EO and UV-C's synergistic effect may be associated with a greater degree of damage to microbial cells compared with the utilization of the technologies separately: combined treatment increases cell permeability and causes more leakage of constituents (Park et al, 2018). In biofilms, EOs may cause structural damages and produce a flatter structure, which, in turn, allow for a higher inactivation rate of UV-C due to increased accessibility to the microbial cells (Silva-Espinoza et al, 2020). Based on these studies' results, UV-C may have a synergistic effect in combination with EO (cinnamon, citral with vanillin, and clove) for purposes of inactivation of foodborne pathogens (Salmonella, Listeria), spoilage (Lactiplantibacillus plantarum), and molds (Rhizopus oryzae and Aspergillus niger) in food products (fresh-cut red chard, juice blends, and fruits) and on surfaces.…”
Section: Essential Oils and Ultraviolet Lightmentioning
confidence: 99%
“…Treatment with 1.2 mg/ml of clove EO followed with UV-C (76.41 mJ/cm 2 ) induced a synergistic effect and resulted in no surviving cells (6.8 log CFU/cm 2 ) embedded within the biofilms. It was demonstrated that the contact with clove EO made the cell easily accessible by UV-C due to the morphological damage occurring: flatter structure ( 109 ).…”
Section: Non-thermal Technologies and Their Combinations With Natural Compounds In Poultry Processingmentioning
confidence: 99%